Pendekatan outcome-based education dalam kurikulum Pendidikan Agama Islam: Studi implementasi dan evaluasi - Sholeh, Ahmad; Murhayati, Sri (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
Curriculum development is crucial to bridging the gap between graduate competencies and labor market demands, particularly amid rapid advancements in science and technology. This study aims to examine the Outcome-Based Education (OBE) approach within the Islamic Religious Education (IRE) curriculum, with a specific focus on its implementation strategies and curriculum evaluation models. Using a qualitative library research method, data were gathered from various sources including documents, journals, books, and academic articles. The findings reveal that the OBE-based IRE curriculum is oriented toward achieving specific learning outcomes (CPL) through the use of case method and project-based learning. The Provus Discrepancy Evaluation Model was used to assess the alignment of curriculum implementation with established standards. These findings imply the need for a more contextual and responsive IRE curriculum design in addressing 21st-century challenges. The study recommends enhancing teacher training on OBE strategies and adjusting curriculum structures to better align with evolving professional demands.